Challenges and facilitators to evidence-based decision-making for maternal and child health in Mozambique: district, municipal and national case studies - Celso Inguane; Talata Sawadogo-Lewis; Eusébio Chaquisse; Timothy Roberton; Kátia Ngale; Quinhas Fernandes; Aneth Dinis; Orvalho Augusto; Alfredo Covele; Leecreesha Hicks; Artur Gremu; Kenneth Sherr (BMC, 2020)
Abstract Background The need for evidence-based decision-making in the health sector is well understood in the global health community. Yet, gaps persist between the availability of evidence and the use of that evidence. Most research on evidence-based decision-making has been carried out in higher-income countries, and most studies look at policy-making rather than decision-making more broadly. We conducted this study to address these gaps and to identify challenges and facilitators to evidence-based decision-making in Maternal, Newborn and Child Health and Nutrition (MNCH&N) at the municipality, district, and national levels in Mozambique. Methods We used a case study design to capture the experiences of decision-makers and analysts (n = 24) who participated in evidence-based decision-making processes related to health policies and interventions to improve MNCH&N in diverse decision-making contexts (district, municipality, and national levels) in 2014-2017, in Mozambique. We examined six case studies, at the national level, in Maputo City and in two districts of Sofala Province and two of Zambézia Province, using individual in-depth interviews with key informants and a document review, for three weeks, in July 2018. Results Our analysis highlighted various challenges for evidence-based decision-making for MNCH&N, at national, district, and municipality levels in Mozambique, including limited demand for evidence, limited capacity to use evidence, and lack of trust in the available evidence. By contrast, access to evidence, and availability of evidence were viewed positively and seen as potential facilitators. Organizational capacity for the demand and use of evidence appears to be the greatest challenge; while individual capacity is also a barrier. Conclusion Evidence-based decision-making requires that actors have access to evidence and are empowered to act on that evidence. This, in turn, requires alignment between those who collect data, those who analyze and interpret data, and those who make and implement decisions. Investments in individual, organizational, and systems capacity to use evidence are needed to foster practices of evidence-based decision-making for improved maternal and child health in Mozambique.